Manipal manual of clinical biochemistry - Nayak B, Shivananda (Jaypee Brothers Medical Publishers, 2013)
A textbook will be improved only by successive revisions. I tired to keep up my promise of revising this book every two-three years. I always respect the suggestions and constructive criticims that come from the readers.